2020
DOI: 10.1136/bmjopen-2019-032268
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific and age-specific characteristics of body composition and its effect on bone mineral density in adults in southern China: a cross-sectional study

Abstract: ObjectivesThis study was an attempt to investigate the variation trend of body composition with ageing and explore the association between regional body composition and bone mineral density (BMD).DesignCross-sectional study.Setting and participantsA total of 5749 healthy adults aged 20–95 years was recruited from 2004 to 2017.Primary outcome measuresWhole-body lean mass (LM), fat mass (FM), android FM, gynoid FM, appendicular lean mass (ALM) and BMD in the lumbar spine, femoral neck and total hip were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…While increases in bone mass were observed with rising total FM in this analysis, BMD values for most analyzed regions were negatively correlated with central fat accumulation, as measured based on AOI, in non-obese postmenopausal elderly women. These findings are consistent with those from other studies suggesting that DXA-based AOI values are negatively correlated with bone health ( 16 18 ). This result may be attributable to a few underlying mechanisms.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…While increases in bone mass were observed with rising total FM in this analysis, BMD values for most analyzed regions were negatively correlated with central fat accumulation, as measured based on AOI, in non-obese postmenopausal elderly women. These findings are consistent with those from other studies suggesting that DXA-based AOI values are negatively correlated with bone health ( 16 18 ). This result may be attributable to a few underlying mechanisms.…”
Section: Discussionsupporting
confidence: 93%
“…After menopause, woman commonly exhibit changes in body composition consisting of a reduction in gynoid fat together with an increase in central fat in the android region ( 14 , 15 ). The android-to-gynoid fat ratio (AOI) has thus been reported to be a valuable indicator of central (visceral) fat accumulation that is correlated with BMD, but studies have yielded inconsistent findings regarding such a relationship ( 16 20 ). Shao et al., for example, found central fat accumulation to be negatively correlated with BMD ( 18 ), whereas Kapus et al.…”
Section: Introductionmentioning
confidence: 99%
“…Age and BMI-adjusted partial correlation indicated that total LM had a significant positive correlation with BMD at different regions, and this agreed with the findings of several other studies ( 29 , 38 ). A study by Xiao et al ( 27 ) among women (20–95 years), reported that total LM had a greater protective effect on BMD in premenopausal women. They concluded that the effect of LM on BMD could be ascribed to the mechanical influence of muscle, which generates a positive effect on osteogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have attempted to explain their association with BMD ( 21 28 ), although research has provided contradicting findings on the contribution of LM and FM to changes in BMD. Some studies have asserted a positive association between LM and BMD ( 27 , 29 ), while others ( 17 ) found that LM, rather than FM, was the strongest predictor of BMD. In contrast, some studies showed that FM ( 30 ) and android /gynoid fat mass ratio (A/G FMR) were positively associated with BMD ( 22 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…on the other hand, increased age can bring about changes of bone geometry, which is mainly manifested as bone expansion [ 22 ]. Furthermore, aging is associated with gradual changes in body composition, typically characterised by decreases in appendicular lean mass and increases in central fat mass [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%